Efficacy and safety of Wuhu oral liquid in treating acute soft tissue injuries: a multicenter, randomized, double-blind, double-dummy, parallel-controlled trial - Zhu, Wen-Hao; Shen, Yi; Xiao, Yu; Shi, Qi; Fan, Zhao-Xiang; Feng, Yan-Qi; Wan, Hong-Bo; Qu, Bo; Zhao, Jun; Zhang, Wei-Qiang; Xu, Guo-Hui; Wu, Xue-Qun; et al. (Frontiers in Pharmacology, 2024)
To evaluate the efficacy and safety of WHOL in treating acute soft tissue injury associated with qi stagnation and blood stasis syndrome and to provide a basis for applying for the protection of varieties of Chinese medicine for WHOL.This study was a randomized, controlled, double-blind, multicenter clinical trial in which Fufang Shang Tong Capsule (FFSTC) was selected as the control drug. 480 subjects with acute soft tissue injury associated with qi stagnation and blood stasis syndrome were randomly divided into a test and control group in a 3:1 ratio. The duration of drug treatment was 10 days. The primary outcome was Visual Analogue Scale (VAS) score for pain (including pain at rest and pain on activity). Secondary outcomes included the disappearance time of the pain at rest and on activity; the curative effect of TCM syndrome and improvement in the individual symptoms of TCM (swelling, ecchymosis, and dysfunction); and changes in Creactive protein (CRP) and interleukin-6 (IL-6) levels. Safety was assessed using vital signs, laboratory examinations, electrocardiograms, and physical examinations.Patient compliance was satisfactory in both groups. After 4 days of treatment, the WHOL group was superior to the FFSTC group in decreasing the VAS scores for pain at rest and on activity. After 7 days of treatment, the WHOL group was superior to the FFSTC group in decreasing the VAS scores for pain on activity and improving swelling. After 10 days of treatment, the WHOL group was superior to the FFSTC group in decreasing the levels of CRP and improving the TCM syndrome and swelling. The disappearance time of pain at rest was 8 days in both groups and 9 days on activity in both groups. In addition, there was no statistical difference between the incidence of adverse events and adverse reactions between the WHOL group and the FFSTC group. No serious adverse events occurred in either group, and no subjects were withdrawn .WHOL relieves the symptoms caused by acute soft tissue injury associated with qi stagnation and blood stasis syndrome more rapidly than FFSTC, and it is effective and safe in the treatment of acute soft tissue injury.